Evading danger: the crisis impact framework for real estate - Tähtinen, Lassi; Toivonen, Saija; Rashidfarokhi, Anahita (International Journal of Strategic Property Management, 2023)
With continuing urbanisation, real estate (RE) has become increasingly important in crisis management. The field of crisis research is still fragmented, especially in the RE context and focuses on the retrospective analysis of single crisis events. This qualitative, futures studies–based paper aims to build a more holistic, foresight-driven understanding of how diverse crises affect RE. It identifies 128 possible future crises from a societal perspective and adopts a novel method in the field, the Futures Wheel, to collect the views of 179 practicing and academic experts via 58 multidisciplinary workshops to analyse the impacts of the identified crises. From this analysis emerged the Crisis Impact Framework for Real Estate, which includes 23 impact themes that synthesise the variety of direct and indirect crisis impacts on RE’s hard elements (e.g. the physical condition of materials) and soft elements (e.g. economic value changes). This study contributes an integrated and foresight-driven perspective to the existing research literature. The framework can assist RE market participants in preparing and assessing critical elements of RE before, during and after crisis impacts have manifested and can help spatial planners, investors and RE managers to reflect in a more multidimensional manner on their vulnerabilities and crisis preparedness.